Evaluating the Quality of STEM-PjBL Learning Materials on Stoichiometry Supported by a Simple Photometer: An Aikens Index Approach - Safitri, Mayliana Ariyani; Eko Setyowati, Widiastuti Agustina; Adeoye, Moses Adeleke; Shidiq*, Ari Syahidul (Universitas Syiah Kuala, 2025)
The development of STEM-project-based learning (STEM-PjBL) materials demands rigorous validation to ensure their quality, effectiveness, and relevance to learning objectives, particularly in complex chemistry topics such as stoichiometry. However, many existing tools lack rigorous validation, potentially undermining the credibility of both research outcomes and educational practices. This study aims to evaluate the quality of STEM-PjBL learning materials on stoichiometry supported by a simple photometer, by assessing the content validity of various instructional and assessment instruments using Aikens Index. A quantitative document analysis approach was employed, with validation conducted through a focus group discussion (FGD) involving seven experts: four chemistry education lecturers from Sebelas Maret University and Padang State University, and three experienced high school chemistry teachers from Surakarta. The instruments evaluated included a teaching module, student worksheet, STEM-PjBL implementation and sustainability literacy questionnaire, sustainability literacy pre-test and post-test, observation sheet for student performance during practicum, water filtration project scoring rubrics, and a cognitive pre-test and post-test on stoichiometry. Expert judgments focused on the clarity, relevance, and alignment of each item with intended learning indicators. The Aikens V coefficient was used to measure inter-rater agreement, with a threshold of 0.76 indicating acceptable content validity. All instruments met the criteria for high content validity. These findings confirm that the developed STEM-PjBL materials and assessment tools are valid and suitable for classroom implementation, offering strong support for enhancing students conceptual understanding, performance skills, and sustainability literacy in chemistry education